The identification and impact of justice risks to commercial risks in the energy sector: post COVID-19 and for the energy transition. Issue 4 (2nd October 2021) - Heffron, Raphael; Connor, Rory; Crossley, Penelope; Mayor, Vicente López-Ibor; Talus, Kim; Tomain, Joseph
Abstract : The energy sector faces many challenges today, in particular from the current health (COVID-19) and resulting financial crises. However, a significant number of challenges existed prior to the outbreak of COVID-19. The approach here is to align academic and practitioner legal research and illuminate for the business world from a legal perspective what the key commercial risks are for the energy sector in the years ahead. A further aim of this article is to demonstrate to interdisciplinary energy researchers how these commercial risks can influence energy activity and decision-making across the world at local, national and international levels. Often those in science or social science do not realise the vital role law plays in reducing or increasing the risk profile of energy activity. And that, in essence, is what this article aims to address: the knowledge gap around law and risk and how interdisciplinary scholars should understand the issue of commercial risk in the energy sector. This article identifies how commercial risk for the energy sector will change due to what can be classed as 'justice risks'. Resolving these justice risks will be necessary over the lifetime of a project from planning through construction, operation and decommissioning phases. For all stakeholders in the energy sector it is vital that there is a recovery and that new energy projects are built and that they contribute to a country's 2030 energy and climate goals. As the world faces the ongoing challenges of the COVID-19, financial and energy-climate crises, ensuring engagement with justice risks can provide a pathway forward to ensure investors commit to investment. Energy, a key sector in the global economy, will be affected but at the same time can enable economic recovery. It can be stated, therefore, that energy has a dual nature – rather like the health sector – being part of the problem but also the solution to the current financial crises (ie the panacea ).